The timing of moult in males and females of the monomorphic Pale-winged Starling Onychognathus nabouroup - (:unkn) unknown (My University, 2015)
Pale-winged Starlings Onychognathus nabouroup inhabit the arid western interior of southern Africa and moult– breeding overlap may occur. We collected field data in two successive years on the moult of individual birds, whose sex was confirmed by genetic techniques. Small samples revealed a non-significant tendency for the moult of females in the early stages of wing moult to be more advanced than that of males in both years, but also clear evidence that the starting date of moult differed in the two years. In this species the moult schedule may thus be variable at both the individual and the population levels.
Keywords: African Research